Effect of energy supplementation on growth performance of Dorper sheep fed with palm kernel cake as a basal diet - Saeed, Osama Anwer; Sazili, Awis Qurni; Akit, Henny; Alimon, Abdul Razak; Samsudin, Anjas Asmara @ Ab Hadi (UB Press, 2016)
A 120-day feeding trial was carried out to evaluate the efficiency of energy in diets for Dorper sheep. A total of 27 six-month old lambs were divided into three groups of nine each. Treatment 1 (control diet) was formulated according to NRC (1985) to meet the body requirements of 75.3% PKC + 0% energy; T2: 70.3% PKC + 5% energy; and T3: 65.3% PKC + 10% energy. The results reveal that the average weight daily gain, feed consumption, and FCR of lambs in the group consuming 10% energy was significantly higher (P<0.05) than those of T2 and T1. Among treatments the final live weight was not influenced (P>0.05) by energy. However, the growth performance of T2 and T3 were comparable to those of T1.